2018
DOI: 10.1186/s13148-018-0441-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of HIV-1 latency: focus on polycomb group (PcG) proteins

Abstract: HIV-1 latency allows the virus to persist until reactivation, in a transcriptionally silent form in its cellular reservoirs despite the presence of effective cART. Such viral persistence represents a major barrier to HIV eradication since treatment interruption leads to rebound plasma viremia. Polycomb group (PcG) proteins have recently got a considerable attention in regulating HIV-1 post-integration latency as they are involved in the repression of proviral gene expression through the methylation of histones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 207 publications
(265 reference statements)
0
27
0
Order By: Relevance
“…We found that many proteins restricted the activity of HIV-1 promoter based on the expression level of luciferase upon knockdown each target (Figure 1A). The top hit proteins included HP1α, GLP, SUZ12 and CYLD, which have been identified to inhibit HIV-1 transcription (Ding et al, 2013; Khan et al, 2018; Manganaro et al, 2014). Intriguingly, we found that knockdown of two less-defined SUMOylation pathway genes TRIM28 and SUMO4 significantly upregulated HIV-1 promoter activity (Figure 1A, Figure 1—figure supplement 1A–B).…”
Section: Resultsmentioning
confidence: 99%
“…We found that many proteins restricted the activity of HIV-1 promoter based on the expression level of luciferase upon knockdown each target (Figure 1A). The top hit proteins included HP1α, GLP, SUZ12 and CYLD, which have been identified to inhibit HIV-1 transcription (Ding et al, 2013; Khan et al, 2018; Manganaro et al, 2014). Intriguingly, we found that knockdown of two less-defined SUMOylation pathway genes TRIM28 and SUMO4 significantly upregulated HIV-1 promoter activity (Figure 1A, Figure 1—figure supplement 1A–B).…”
Section: Resultsmentioning
confidence: 99%
“…The small molecule C646 also achieves this effect, by specifically inhibiting p300 and CBP histone acetyltransferases 63 . Drugs that modify epigenetic regulation have also been developed to treat patients with cancer or viral infections 6466 . These agents might be used to inactivate cccDNA in infected hepatocytes.…”
Section: Hbv Life Cycle and Therapeutic Targetsmentioning
confidence: 99%
“…Interestingly, the integrated provirus in those cells is subjected to transcriptional silencing by host chromatin-modifying enzymes, comprising deacetylases, methyltransferases, and others [19]. This paved the road to the emergence of two new epigenetic therapeutic approaches, namely the “shock and kill” and the “block and lock” strategies [2023]. Here, we present general points about these two anti-HIV therapeutic strategies (Fig.…”
Section: Hiv and Epigenetics A Leading Example As A Proof Of Conceptmentioning
confidence: 99%